Cancer and vitamin C - Chen, Qi; Vissers, Margreet C. M. (Margreet Catherina Maria) (Boca Raton, FL : CRC Press, 2020)
Vitamin C may offer significant therapeutic benefits in the treatment of cancer. This book includes chapters by a group of leading scientific researchers documenting the ways cancer can be affected by high doses of ascorbate. After an initial chapter providing a historical perspective, subsequent chapters focus on cancer cell death, reprogramming of somatic cells, recent case studies, and other ways vitamin C can improve outcomes of therapy. Features Includes chapters from a team of leading international scholars Reviews the history of beneficial uses of vitamin C in the treatment of cancer Summarizes recent case studies Discusses how vitamin C may synergistically affect other cancer treatment methods
Part I Historical Overview of Cancer and Vitamin C. 1. Introduction to Vitamin C and Cancer Clinical Studies: A Historical Perspective. Part II Mechanims of Action for Vitamin C in Cancer. 2. High-Dose Intravenous Ascorbate as a Pro-Oxidant Inducing Cancer Cell Death. 3. Pharmacological Ascorbate Influences Multiple Cellular Pathways Preferentially in Cancer Cells. 4. Ascorbate and the Hypoxic Response in Cancer. 5. Pharmacological Ascorbate as a Radiosensitizer. 6. Vitamin C and Somatic Cell Reprogramming. Part III Vitamin C and Cancer Clinical Studies. 7. Vitamin C and Cancer: An Overview of Recent Clinical Trials. 8. Orthomolecular Approaches for the Use of Intravenous Vitamin C: Administration by Integrative and Naturopathic Doctors.
OCLC-licensed vendor bibliographic record.
Keywords: Vitamin C -- Therapeutic use; Cancer -- Chemotherapy; MEDICAL / Biochemistry; MEDICAL / Oncology; SCIENCE / Life Sciences / Biochemistry